Historic churches of Barbados - Hill, Barbara, ed. (Art Heritage Publications BridgetownBB, 1984)
Gives historical profile and architectural detail of various churches and cathedrals in Barbados. Tributes to the life and work of architect Barbara Hill and builder William Hart Coleridge are given. Promotes restoration and preservation of this aspect of Barbadian cultural heritage.